The Effectiveness of the Use of Video-Based Learning Media on Student Learning Motivation on Fable Story Material - Lahagu, Yarni Kristiani; Zebua, Fentri; Bawamenewi, Arozatulo; Harefa, Faona’atulo (World Psychology, 2024)
This study examines the effectiveness of using video-based learning media on student learning motivation on fable story material at Tomosa Christian Private Junior High School. The background of the research shows that learning media can increase students' understanding and interest, but many teachers still do not utilize it optimally. The research method used was qualitative with a descriptive approach, involving observation and written tests. The results showed that the use of videos as learning media was effective in increasing students' motivation and understanding. Videos help visualize fable material, make learning more interesting, and increase student engagement. In conclusion, video-based learning media has a significant positive impact on students' learning motivation, indicating that the integration of technology in education is essential to improve the quality of learning.